Pencegahan Fraud Pengelolaan Dana Desa Dengan Akuntabilitas, Whistle Blowing, Kompetensi Aparatur Dan Pengendalian Internal - Enita Binawati; Junaidi Affan (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
The purpose of this study was to empirically test the effect of accountability, whistleblowing, apparatus competence and the effectiveness of internal control on fraud prevention in managing village funds. The research was conducted at the Village Government in the Province of DIY. The method used in this research is mix methods. The stages of the method are 1). quantitative method by distributing questionnaires to the respondents and continued 2). qualitative method, namely by interviewing the respondents. The analysis tool for model testing uses Partial Least Square (PLS). The results of the quantitative study showed that the prevention of fraud in the management of village funds which was tested on the Village government in the DIY Province proved to be empirically positively influenced by the accountability factor while the whistleblowing factor, apparatus competence, and internal control did not positively affect it. The results of the qualitative research can be concluded from the interview process that it can be concluded that the process of planning, compiling, implementing and reporting village funds in the Village Government of the Village of Kalurahan in the Provincial Government of DIY, as a whole refers to the mechanism of provisions and rules that have been established both at the Regional Regulation level (Perda), District Regulations and Village Regulations of the Village government. The use of village funds and reporting of village funds, regular monitoring and inspection is carried out by other parties or institutions or agencies appointed by the village village administration. In preventing and overcoming fraud in the management and use of village funds, the village government cooperates with the government inspectorate to provide guidance and assistance for routine inspections from the Provincial BPK/BPKP, and Consultants.